A Novel Meshfree Strategy for a Viscous Wave Equation With Variable Coefficients - Wang, Fuzhang; Zhang, Juan; Ahmad, Imtiaz; Farooq, Aamir; Ahmad, Hijaz (Frontiers in Physics, 2021)
A one-step new general meshfree scheme, which is based on radial basis functions, is presented for a viscous wave equation with variable coefficients. By constructing a simple extended radial basis function, it can be directly applied to wave propagation by using the strong form-based meshfree collocation method. There is no need to deal with the time-dependent variable particularly. Numerical results for a viscous wave equation with variable coefficients show that the proposed meshfree collocation method is simple, accurate, stable and computationally efficient.